A case of rectal endometriosis presenting as extramucosal rectal mass - (:unkn) unknown (My University, 2006)
0
Mukoza dışı rektum kitlesi şeklinde ortaya çıkan bir rektum endometriozisi olgusu
Keywords: Cerrahi